2018
DOI: 10.5858/arpa.2017-0524-ra
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Neuronal Dysplasia Type B: An Updated Review of a Problematic Diagnosis

Abstract: Context.-Intestinal neuronal dysplasia type B (IND B) is a controversial histopathologic phenotype that has been associated with intestinal dysmotility, either as an isolated condition or in conjunction with established pathologic disorders (eg, Hirschsprung disease). Many factors contribute to the debate over the existence and/or clinical significance of IND B, including a large body of published data based on inconsistent diagnostic criteria and methods, which have fostered many unwarranted conclusions that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 86 publications
0
27
0
Order By: Relevance
“…Failures in development of ENS and consequent impairments will cause severe intestinal motor disorders, such as the complicated disorder NID. Many investigators have raised doubts about the existence of NID as a distinct histopathologic entity and suggested that the pathologic changes seen in IND may be a secondary phenomenon induced by intestinal obstruction and inflammatory disease [1,21]. The Tlx2 -/mice is a strong evidence that NID is a real entity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Failures in development of ENS and consequent impairments will cause severe intestinal motor disorders, such as the complicated disorder NID. Many investigators have raised doubts about the existence of NID as a distinct histopathologic entity and suggested that the pathologic changes seen in IND may be a secondary phenomenon induced by intestinal obstruction and inflammatory disease [1,21]. The Tlx2 -/mice is a strong evidence that NID is a real entity.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the similar clinical symptoms between NID and HSCR, definitive diagnosis still depends on histopathological analysis of rectal biopsies nowadays [1]. Rectal biopsy is a skillful and delicate method which only gives excellent results if it is carried out by a very competent surgeon [29].…”
Section: Gastroenterology Research and Practicementioning
confidence: 99%
See 2 more Smart Citations
“…IND-B is a rare disease that remains surrounded by several controversies ranging from its definition as a real disease to the different criteria for its diagnosis and treatment options 2,7,30 . Faced with all these uncertainties, physicians are routinely challenged about what to do with the results of rectal biopsies that reveal submucosal nerve plexus hyperplasia, leading to the diagnosis of IND-B in patients with severe constipation or intestinal obstruction 7 .…”
Section: Discussionmentioning
confidence: 99%